Contemporary issues of transboundary water utilisation in Central Asia: political and legal analysis - Kenjayev Amirbek Alijon Ugli; Madaminova Durdona Iskandarovna; Abdullayev Khurshid Nazrullaevich; Kuralbayev Almas Ahmetkarimovich (Legality : Jurnal Ilmiah Hukum, 2025)
This article examines the formation and development of the organisational and legal framework governing the joint use of transboundary water resources in Central Asia. The evolution of international legal instruments in transboundary water management, along with the ecological issues that accompany it, was analysed systematically using political-legal approaches and comparative historical studies. Contemporary sources and historical chronicles of the last three decades required in this study include publications of domestic and international organisations. Special focus is given to the legal regulation surrounding the construction of the controversial Kushtepa Canal. In conclusion, reaching a consensus among regional states is key to maintaining regional stability and security. The article also proposes the establishment of regional cooperation mechanisms and increasing data transparency as solutions to the challenges of water management in Central Asia.